A hybrid cascade converter topology with series-connected symmetrical and asymmetrical diode-clamped H-bridge cells - Nami, A.; zare, F.; Ghosh, Arindam; Blaabjerg, F. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2011)
A novel H-bridge multilevel pulsewidth modulation converter topology based on a series connection of a high-voltage diode-clamped inverter and a low-voltage conventional inverter is proposed in this paper. A dc link voltage arrangement for the new hybrid and asymmetric solution is presented to have a aximumnumber of output voltage levels by preserving the adjacent switching vectors between voltage levels. Hence, a 15-level hybrid converter can be attained with a minimum number of power components. A comparative study has been carried out to present high performance of the proposed configuration to approach a very low total harmonic distortion of voltage and current, which leads to the possible elimination of the output filter. Regarding the proposed configuration, a new cascade inverter is verified by cascading an asymmetrical diode-clamped inverter, in which 19 levels can be synthesized in output voltage with the same number of components. To balance the dc link capacitor voltages for the maximum output voltage resolution as well as synthesize asymmetrical dc link combination, a new multi-output boost converter is utilized at the dc link voltage of a seven-level H-bridge diode-clamped inverter. Simulation and hardware results based on different modulations are presented to confirm the validity of the proposed approach to achieve a high-quality output voltage.